The Mussel Mytilus galloprovincialis in the Bay of Naples: New Insights on Oogenic Cycle and Its Hormonal Control. Issue 6 (22nd February 2019) - Rosati, Luigi; Agnese, Marisa; Abagnale, Ludovico; Aniello, Francesco; Andreuccetti, Piero; Prisco, Marina
ABSTRACT: The aim of the present article was to investigate the oogenic cycle of Mytilus galloprovincialis sampled in the Bay of Naples, and to immunolocalize 3β‐hydroxysteroid dehydrogenase (3β‐HSD), 17β‐hydroxysteroid dehydrogenase (17β‐HSD), and P450 aromatase, enzymes involved in the synthesis of two sex hormones: testosterone and 17β‐estradiol. We demonstrate that the oogenic cycle starts in late summer‐early fall and continues in early winter when the first event of spawning occurs; other spawning events take place until June, when the ovary is spent and contains a few empty ovarian follicles and numerous somatic cells, that is, adipogranular cells and vesicular connective tissue cells. During the oogenic cycle, apoptotic events occur at the level of oogonia, previtellogenic oocytes, as well as follicle cells; by contrast, necrosis events probably take place in vitellogenic oocytes, which, once degenerated, transfer their content to healthy oocytes. Finally, the present data demonstrate that 3β‐HSD, 17β‐HSD, and P450 aromatase are present in the ovary both during the reproductive and nonreproductive phases. The possible role of these enzymes during the Mytilus galloprovincialis reproductive cycle is discussed. Anat Rec, 302:1039–1049, 2019. © 2019 Wiley Periodicals, Inc.